Doctor Strange [videorecording (Blu-Ray)] - Derrickson, Scott; Cumberbatch, Benedict, 1976-; Ejiofor, Chiwetel, 1977-; McAdams, Rachel, 1978-; Wong, Benedict; Stuhlbarg, Michael; Bratt, Benjamin, 1963-; Adkins, Scott, 1976-; Mikkelsen, Mads, 1965-; Swinton, Tilda; Lee, Stan, 1922-2018 (Marvel Studios, 2017)
A former neurosurgeon embarks on a journey of healing only to be drawn into the world of the mystic arts.